THE ROLE OF THE COMMUNITY IN THE DEVELOPMENT OF MANGROVE FOREST ECOTOURISM IN PASAR BANGGI, REMBANG REGENCY - Sholeh, Sofyan; Evianovita, Dwi Intan Nur; Mayasari, Annita Yuli; Sudewo, Anung Ari (Indonesian Journal of Environment and Disaster, 2024)
Mangrove forests are one of the most productive ecosystems, located in tropical and subtropical coastal waters and river estuaries. Mangroves provide benefits to humans and the environment by providing shelter for brackish water organisms such as fish and shrimp. Pasar Banggi Mangrove Forest in Rembang Regency has a geographic location with a geographical position of 6º41'52.45 "- 6º41'52.66" LS and 111º23'19.80"-111º23'20.01" East. The Pasar Banggi area experienced a 353-meter coastline setback due to abrasion. This has resulted in degradation. Given the importance of the function of mangrove forests, it is appropriate to take serious measures to reduce the effects of degradation. One possible utilization effort is through mangrove conservation activities. An appropriate alternative to mangrove conservation to be developed in Pasar Banggi is the development of the ecotourism sector. The purpose of this study was to determine the role of the community and the development of mangrove ecotourism in the Pasar Banggi Mangrove Forest area. The method used in this research is convergent parallel mixed-method. Data collection methods using interviews and FGDs with relevant stakeholders. The results showed that the Pasar Banggi mangrove forest ecosystem was classified as the best ecosystem condition along the Pantura Line. Conservation efforts and community participation in suppressing mangrove degradation in Pasar Banggi Mangrove Forest is the establishment of the Sido Dadi Maju Farmer Group which is fully responsible for mangrove management and mangrove ecotourism development in Pasar Banggi Mangrove Forest.